2013
DOI: 10.1021/np4005322
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Lignans from the Trunk of Abies holophylla

Abstract: Six new lignans (1-6) were isolated from the trunk of Abies holophylla MAXIM, together with 11 known lignans (7-17). The structures of 1-7 were elucidated by spectroscopic methods, acid hydrolysis, and use of the modified Mosher's method. The effects of the isolates on nerve growth factor induction in a C6 rat glioma cell line were evaluated. Compounds 6, 7, and 13 showed significant induction of nerve growth factor secretion at concentrations of 10 μM. Compounds 1, 5, 6, and 16 showed moderate inhibitory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…O-β-D-glucopyranoside (10) [19], bombasin-4-O-β-D-glucopyranoside (11) [19], apigenin- [20], and schaftoside (15) (Table 1, see File 1 in supporting information). The spectroscopic data suggested that 12 was a dihydrobenzofuran neolignan glycoside [19].…”
Section: Resultsmentioning
confidence: 99%
“…O-β-D-glucopyranoside (10) [19], bombasin-4-O-β-D-glucopyranoside (11) [19], apigenin- [20], and schaftoside (15) (Table 1, see File 1 in supporting information). The spectroscopic data suggested that 12 was a dihydrobenzofuran neolignan glycoside [19].…”
Section: Resultsmentioning
confidence: 99%
“…Arisanschinins F-L (97)(98)(99)(100)(101)(102)(103), characterized from the fruits of the Taiwanese medicinal plant Schisandra arisanensis, showed moderate in vitro inhibition of proliferation of peripheral blood mononuclear cells (PBMC) induced by phytohemaglutinin (PHA). 43 The EtOAc extract of fruits of Schisandra chinensis (Turcz.)…”
Section: Dibenzocyclooctadiene Derivativesmentioning
confidence: 99%
“…97 The cytotoxicity of these three lignans ((AE)-, (+)-, and (À)-liriodenols) was evaluated in vitro against four selected human tumor cell lines. It was noticed that (+)-liriodenol showed more signicant cytotoxic effects (IC 50 98 The a,b-unsaturated-glactone lignan procumbiene 252 was isolated from Justicia procumbens L. 70 The leaves of Piper sanguineispicum Trel. (Piperaceae), used in Peru (Loreto Department) as an anti-inammatory remedy, displayed one of the most promising in vitro leishmanicidal activity against axenic amastigote forms of Leishmania amazonensis.…”
Section: Dibenzylbutane Dibenzylbutyrolactol and Dibenzylbutyrolactomentioning
confidence: 99%
“…Our earlier phytochemical investigation on A. holophylla resulted in the isolation of anti-inflammatory lignans. 8 In our continuing search for bioactive constituents from Korean medicinal plants, we further isolated a novel rearranged abietane-type diterpene with spiro [4.5]decane structure, holophyllin A (1), together with a new diterpene glycoside, holophyllin B (2) ( Fig. 1) from the n-hexane and EtOAc-soluble layers of the MeOH extract of A. holophylla, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The D-configuration of sugar was determined by GC/MS analysis. 8 The biogenetic origin of 1 and 2a can plausibly be tracked back to the most common compound, abietic acid (Scheme 1). Allylic oxidation at C-9 and epoxidation at C-7/C-8 and C-13/C-14 of abietic acid generates intermediate i.…”
Section: Introductionmentioning
confidence: 99%